Дослідження можливості дезодорування соняшникового лецитину - Демидова, Анастасія Олександрівна; Гладкий, Федір Ф.; Шеманська, Євгенія Іванівна (My University, 2021)
Для повноцінного виходу на світові ринки соняшникового лецитину необхідно вирішити наступні основні завдання – зниження вмісту механічних домішок, зниження в’язкості та дезодорування лецитину. Завдання зниження інтенсивності запаху і смаку є найскладнішою з них. Соняшниковий лецитин характеризується більш інтенсивним ароматом і смаком, ніж соєвий, з такими сенсорними компонентами: горіховий, карамельний, солодкий, жирний, фруктовий. До складу летких лецитинів входять низькомолекулярні вуглеводні, альдегіди, кетони, лактони, нітрили, спирти. У статті доведено можливість дезодорації фосфатидного концентрату соняшнику шляхом його обробки етиловим спиртом з подальшим вилученням летких речовин в умовах зниженого тиску. При обробці нерафінованого лецитину розчинником із співвідношенням етанол/вода (96:4 або 99,9:0,1) при вмісті розчинника 40% (відносно лецитину) спостерігається ефект дезодорації лецитину.

To fully enter the world markets of sunflower lecithin, it is necessary to solve the following main tasks - reducing the content of mechanical impurities, reducing the viscosity and deodorization of lecithin. The task of reducing the intensity of smell and taste is the most difficult of them. Sunflower lecithin is characterized by a more intense aroma and taste than soy with the following sensory components: nut, caramel, sweet, fatty, fruity. The composition of volatile lecithins includes low molecular weight hydrocarbons, aldehydes, ketones, lactones, nitriles, alcohols. The possibility of deodorization of sunflower phosphatide concentrate by its treatment with ethyl alcohol with the subsequent extraction of volatile substances under conditions of reduced pressure is proved in the article. At the time of treatment of unrefined lecithin with a solvent with a ratio of ethanol / water (96: 4 or 99.9: 0.1) at a solvent content of 40% (relative to lecithin) there is an effect of deodorization of lecithin. As a result of the processing an alcohol-soluble fraction was received (enriched in phosphotidylcholine) in the amount of 23% and an alcohol-insoluble fraction (with a predominant phosphatidylinositol content) in the amount of 77%. The amount of alcohol-soluble fraction can be reduced by using absolute ethyl alcohol up to 13%. Organoleptic evaluation was performed, physicochemical parameters and group composition of phospholipids of lecithin fractions obtained as a result of treatment with ethyl alcohol were studied. The quality indicators of the alcohol-insoluble fraction meet the requirements of SOU 15.4-37-212: 2004 "Phosphatide concentrates. Specifications". Alcohol-soluble fraction meets the requirements of the regulatory document after degreasing with acetone in one stage at a ratio of fraction: acetone as 1: 1.
Keywords: лецитин соняшниковий; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; sunflower lecithin; дезодорація; deodorization; сенсорні характеристики; sensory characteristics; спирт етиловий; ethyl alcohol